Feasibility of a Combination HIV Prevention Program for Men Who Have Sex With Men in Blantyre, Malawi. (1st October 2015) - Wirtz, Andrea L.; Trapence, Gift; Jumbe, Vincent; Umar, Eric; Ketende, Sosthenes; Kamba, Dunker; Berry, Mark; Strömdahl, Susanne; Beyrer, Chris; Muula, Adamson S.; Baral, Stefan
Abstract : Introduction: The use of combination HIV prevention interventions (CHPI) now represent the standard of care to minimize HIV acquisition risks among men who have sex with men (MSM). There has been limited evaluation of these approaches in generalized HIV epidemics and/or where MSM are stigmatized. A peer-based CHPI program to target individual, social, and structural risks for HIV was developed for MSM in Blantyre, Malawi. Methods: To test the feasibility of CHPI, adult MSM were followed prospectively from January 2012 to May 2013. Participants (N = 103) completed sociobehavioral surveys and HIV testing at each of the 3 follow-up study visits. Results: Approximately 90% of participants attended each study visit and 93.2% (n = 96) completed the final visit. Participants met with peer educators a median of 3 times (range: 1–10) in the follow-up visits 2 and 3. Condom use at last sex improved from baseline through follow-up visit 3 with main (baseline: 62.5%, follow-up 3: 77.0%; P = 0.02) and casual male partners (baseline: 70.7%, follow-up 3: 86.3%; P = 0.01). Disclosure of sexual behaviors/orientation to family increased from 25% in follow-up 1 to 55% in follow-up 3 ( P < 0.01). Discussion: Participants maintained a high level of retention in the study highlighting the feasibility of leveraging community-based organizations to recruit and retain MSM in HIV prevention and treatment interventions in stigmatizing settings. Group-level changes in sexual behavior and disclosure in safe settings for MSM were noted. CHPI may represent a useful model to providing access to other HIV prevention for MSM and aiding retention in care and treatment services for MSM living with HIV in challenging environments. Abstract : Supplemental Digital Content is Available in the Text.